The effect of goods and services tax and corruption control on inflationary episode - Chan, Sok Gee; Ramly, Zulkufly (2019)
This study aims to model the effect of tax reform on inflation, focusing on the indirect tax regime or known as GST or VAT in some countries. Malaysia had undergone two major tax reforms in the past three years starting from the shift from SST to GST in April 2015. In September 2018, the government reverted to the SST system. Any form of new tax affects businesses and consumers alike. Nobody likes paying taxes. Any form of taxation is likely to be opposed. On the government side, the motive for imposing GST was to enhance tax collection efficiency, thus raising tax revenue for the government. Meanwhile, businesses and consumers generally opposed GST because it increased business costs, which then transferred to consumers in the form of higher prices. In view of this background, this paper has three main objectives. The first objective is to investigate the impact of GST on the inflationary episode over the period of 2012-2017 in Malaysia. Next, using global data from countries with a VAT system, this study has examined the overall impact of VAT, exchange rate and crude oil price on inflationary episodes in the world. Recognizing the importance of governance in the tax administration, this study had also examined the role of control for corruption in the relationship between VAT, exchange rate and crude oil price on an inflationary episode in the world. Key findings of the study are as follows: (i) The general CPI in Malaysia had been on an upward trend during the period of 2012-2017. (ii) The pull factors of inflation in Malaysia were food, restaurant, and hotel, health and services sectors. The real impact of GST on food prices was visible six months after April 2015. (iii) GST alone did not increase CPI in Malaysia. The softening of MYR increased the prices of imported goods particularly food and healthcare products. The decline of crude oil prices did not reduce prices. The higher business cost arising from GST and depreciation of MYR possibly offset the effect of a lower cost of production due to the decline in the crude oil price. (iv) VAT led to an inflationary episode in the countries with the VAT system. The impact of VAT on inflation was greater in the middle and lower-income countries than those in high-income countries. (v) A stronger corruption control was likely to cushion the adverse effect of VAT on inflation across sample countries. (vi) The favourable effect of corruption control on inflation weakened after controlling for the effects of currency depreciation and crude oil price. (vii) Corporate tax led to higher inflation in Malaysia over the period of 1980-2016. Meanwhile, the sales tax and excise tax decreased inflation over the same period.